Pengaruh Edukasi Menggunakan Media Leaflet Terhadap Kecemasan Wanita Menopause Di Wilayah Kerja Puskesmas Jembatan Kecil Kota Bengkulu Tahun 2026 - Selvia Antasari; Des Metasari; Murwati Murwati (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Menopause is the phase of permanent cessation of menstruation, which can cause anxiety due to a lack of knowledge about the physical and psychological changes that occur. This study aims to determine the effect of education using leaflets on the anxiety of menopausal women in the working area of the Jembatan Kecil Community Health Centre in Bengkulu City in 2026. The study used a quasi-experimental pre-post test one group design. The population consisted of menopausal women aged 45–55 years registered at the Jembatan Kecil Community Health Centre in 2026 (n = 442), with a sample of 18 respondents selected through purposive sampling. The instruments used were the Hamilton Anxiety Rating Scale (HARS) questionnaire to measure anxiety and leaflets as educational media. Data analysis was performed using the Wilcoxon Signed Ranks Test after the Shapiro-Wilk normality test. The results showed that before education, the average anxiety score was 1.06, ranging from no anxiety to moderate anxiety. After education, the average anxiety score decreased to 0.67 with no respondents experiencing moderate anxiety. The Wilcoxon test obtained a Z value of -2.333 with a significance of p = 0.020 (